CD4+ T-Cell Activation Prompts Suppressive Function by Extracellular Vesicle-Associated MicroRNAs - Di Silvestre, Dario; Garavelli, Silvia; Procaccini, Claudio; Prattichizzo, Francesco; Passignani, Giulia; De Rosa, Veronica; Mauri, Pierluigi; Matarese, Giuseppe; de Candia, Paola (Frontiers in Cell and Developmental Biology, 2021)
MicroRNAs (miRNAs), small non-coding molecules targeting messenger RNAs and inhibiting protein translation, modulate key biological processes, including cell growth and development, energy utilization and homeostasis. In particular, miRNAs control the differentiation, survival and activation of CD4+ T conventional (Tconv) cells, key players of the adaptive immunity, and regulate the physiological response to infections and the pathological loss of immune homeostasis in autoimmunity. Upon T cell receptor (TCR) stimulation, the described global miRNA quantitative decrease occurring in T cells is believed to promote the acquisition of effector functions by relaxing the post-transcriptional repression of genes associated to proliferation and cell activity. MiRNAs were initially thought to get down-regulated uniquely by intracellular degradation; on the other hand, miRNA secretion via extracellular vesicles (EVs) represents an additional mechanism of rapid down-regulation. By focusing on molecular interactions by means of graph theory, we have found that miRNAs released by TCR stimulated Tconv cells are significantly enriched for targeting transcripts up-regulated upon stimulation, including those encoding for crucial proteins associated to Tconv cell activation and function. Based on this computational approach, we present our perspective based on the following hypothesis: a stimulated Tconv cell will release miRNAs targeting genes associated to the effector function in the extracellular space in association with EVs, which will thus possess a suppressive potential toward other Tconv cells in the paracrine environment. We also propose possible future directions of investigation aimed at taking advantage of these phenomena to control Tconv cell effector function in health and autoimmunity.